Artificial Neural Network Untuk Memprediksi Beban Listrik Dengan Menggunakan Metode Backpropagation - Dermawan, Heri; Ishak Alkadri, Syarif (entries, 2025)
PT PLN Area Ketapang West Kalimantan is a State-Owned Enterprise engaged in the provision of Electricity Resources in Ketapang, West Kalimantan. Prediction of future electricity needs is an important part, in order to meet electricity needs in Ketapang. Artificial Neural Network uses the Backpropagation method applied in this study to predict electricity load needs, it is expected to help in solving this problem. This electricity usage load prediction is influenced by input data on the amount of customer power from various sectors so that the amount of electricity load is known as the target. The data used is electricity sales report data from 2012 - 2016 PT. PLN Area Ketapang. Implementation of the artificial Neural Network backpropagation method using Matlab 8.5 as supporting software